In vitro pharmacological investigation of fruit of Acacia nilotica - Shinde, Pradnya; Kadav, Shraddha; Kamble, Ashwini; Tamboli, Ashpak (Indian Journal of Pharmacy & Drug Studies, 2023)
The famous medium-sized Acacia nilotica tree, often known locally as "Babul" or "Kikar," is widely distributed throughout tropical and subtropical regions. It has a wide variety of possible medical applications and antioxidant action. This study's goal was to ascertain the fruits of Acacia nilotica's Invitro anti-inflammatory and antioxidant activities. Acacia nilotica hydroalcoholic extract's Invitro anti-inflammatory and anti-oxidant activities were assessed. The significant activity of Inhibition of Protein denaturation shown a maximum of 76% inhibition at 500 μg/ml concentration. From the hydroalcoholic extract 400 g/ml showed a maximum of 99.85% of DPPH radical scavenging activity.